If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3-(x-1)=-2-3(5x-x)
We move all terms to the left:
3-(x-1)-(-2-3(5x-x))=0
We add all the numbers together, and all the variables
-(x-1)-(-2-3(+4x))+3=0
We get rid of parentheses
-x-(-2-3(+4x))+1+3=0
We calculate terms in parentheses: -(-2-3(+4x)), so:We add all the numbers together, and all the variables
-2-3(+4x)
determiningTheFunctionDomain -3(+4x)-2
We multiply parentheses
-12x-2
Back to the equation:
-(-12x-2)
-1x-(-12x-2)+4=0
We get rid of parentheses
-1x+12x+2+4=0
We add all the numbers together, and all the variables
11x+6=0
We move all terms containing x to the left, all other terms to the right
11x=-6
x=-6/11
x=-6/11
| 2w+4=w+73 | | 2^(2x)-2^x=-4 | | 2-4/9x=5/6 | | 3/7x=3x+3/30x-6 | | (X/x-3)+2=-12/x^2-9 | | k/8+-14=-18 | | 4b+94=8b+82 | | h/10+83=88 | | 8^(3-7n)+10=94 | | -0.75-6=0.25p | | 7-4y=2y+31 | | h10+ 83= 88 | | 9n-6=10n | | 1-x-2=3x | | X2+10x21=0 | | 27+6m=8.25m | | 8(3-7n)+10=94 | | 9n-6=10 | | 40-27y=-14 | | 8b=56.80 | | 4/3x2=-1 | | 4.1-7z=3.6 | | 24=3r4 | | 53=9u-19 | | 7-3x-3=8+x | | X2+X3+x4+x5=0 | | 53=9u-9 | | -13=-3+2x | | 12+3x=x+14 | | -a/7=21 | | 4x-4=-3x+25 | | n/11=33 |